Segmental arterial mediolysis: vasculopathy presenting as acute abdominal pain - Pulandran, Sahilan; Ramachandren, Thavenesh; Puckridge, Phillip (International Surgery Journal, 2024)
Segmental arterial mediolysis, initially termed segmental mediolytic arteritis, is a rare noninflammatory, non-atherosclerotic vasculopathy that primarily affects visceral arteries. SAM presents with a unique skip pattern of arterial involvement and is characterized by the degeneration of the arterial medial layer, leading to various vascular abnormalities. We present the case of a fit and healthy 50-year-old Male who sought medical attention for the sudden onset of severe abdominal pain. This led to the diagnosis of SAM after repeated imaging and blood investigations. The considered differential diagnoses include fibromuscular dysplasia, vasculitis, and mycotic aneurysms. This case underscores the importance of clinical awareness and multidisciplinary collaboration in diagnosis and managing SAM, offering valuable insights into its clinical presentation and the complexities surrounding its diagnosis and treatment. Conclusively, SAM is treated conservatively by emphasizing blood pressure control, antiplatelet therapy, and anticoagulation. However, endovascular intervention is deemed necessary if there is evidence of end-organ ischemia.